Implementation of Authoritative Parenting Patterns on the Independence of 5-6 Year Old Children at the Mathla'ul Huda Ambarawa Pringsewu Early Childhood Education Center - Khadijah Aliatu Rohma; Syekh Al Ngarifin (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the implementation of authoritative parenting and analyze its influence on the independence of children aged 5–6 years at PAUD KB Mathla’ul Huda Ambarawa. Authoritative parenting is an approach that balances warmth, communication, and rational control to optimally support children’s character development. This research employed a descriptive qualitative method involving teachers, the principal, and students as research subjects. Data were collected through observation, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing, and validated through source and technique triangulation. The findings indicate that authoritative parenting is implemented through responsibility habituation, providing children with opportunities to choose activities, two-way communication, and firm yet warm rule enforcement. This implementation positively affects children’s independence, as reflected in their ability to perform daily tasks independently, show self-confidence, discipline, and interact socially. Therefore, authoritative parenting is considered effective in fostering independence and character building in early childhood education